PERENCANAAN STRUKTUR ATAS GEDUNG RUANG KELAS MADRASAH IBTIDAIAH NEGERI ( MIN ) KOTA BUKITTINGGI - Ilham Akbar Renzano; Ishak Ishak; Deddy Kurniawan (Ensiklopedia Research and Community Service Review, 2022)
In line with world growth in the construction sector, Indonesia is developing and growing very rapidly. In West Sumatra itself, the need for housing as well as office buildings and learning facilities and infrastructure is currently increasing. Such is the case with "Construction of the Bukittinggi City State Madrasah Ibtidaiah (MIN) Classroom Building". Aims to improve educational facilities and infrastructure. All of this requires planning and building construction that must be standard, safe and efficient. With the current development of a more advanced country, calculating and designing high-rise building structures can be done using the help of the SAP2000 program which is specifically for designing high-rise building structures. In this thesis, the author wants to design the Construction of the Public Madrasah Ibtidaiah (MIN) Classroom Building in Bukittinggi City. Using calculations according to SNI Earthquake 03-1726-2012.